Simultaneous blocking of the pan‐RAF and S100B pathways as a synergistic therapeutic strategy against malignant melanoma. Issue 4 (30th December 2020) - Wu, Ke‐Jia; Ho, Shih‐Hsin; Wu, Chun; Wang, Hui‐Min D.; Ma, Dik‐Lung; Leung, Chung‐Hang
Abstract: Melanoma is a very aggressive form of skin cancer. Although BRAF inhibitors have been utilized for melanoma therapy, advanced melanoma patients still face a low five‐year survival rate. Recent studies have shown that CRAF can compensate for BRAF depletion via regulating DNA synthesis to remain melanoma proliferation. Hence, targeting CRAF either alone or in combination with other protein pathways is a potential avenue for melanoma therapy. Based on our previously reported CRAF‐selective inhibitor for renal cancer therapy, we have herein discovered an analogue (complex 1 ) from the reported CRAF library suppresses melanoma cell proliferation and melanoma tumour growth in murine models of melanoma via blocking the S100B and RAF pathways. Intriguingly, we discovered that inhibiting BRAF together with S100B exerts a novel synergistic effect to significantly restore p53 transcription activity and inhibit melanoma cell proliferation, whereas blocking BRAF together with CRAF only had an additive effect. We envision that blocking the pan‐RAF and S100B/p53 pathways might be a novel synergistic strategy for melanoma therapy and that complex 1 is a potential inhibitor against melanoma via blocking the pan‐RAF and S100B pathways.